Ecomarkets for conservation and sustainable development in the coastal zone. (24th November 2012) - Fujita, Rod; Lynham, John; Micheli, Fiorenza; Feinberg, Pasha G.; Bourillón, Luis; Sáenz‐Arroyo, Andrea; Markham, Alexander C.
ABSTRACT Because conventional markets value only certain goods or services in the ocean (e.g. fish), other services provided by coastal and marine ecosystems that are not priced, paid for, or stewarded tend to become degraded. In fact, the very capacity of an ecosystem to produce a valued good or service is often reduced because conventional markets value only certain goods and services, rather than the productive capacity. Coastal socio‐ecosystems are particularly susceptible to these market failures due to the lack of clear property rights, strong dependence on resource extraction, and other factors. Conservation strategies aimed at protecting unvalued coastal ecosystem services through regulation or spatial management (e.g. Marine Protected Areas) can be effective but often result in lost revenue and adverse social impacts, which, in turn, create conflict and opposition. Here, we describe 'ecomarkets' – markets and financial tools – that could, under the right conditions, generate value for broad portfolios of coastal ecosystem services while maintaining ecosystem structure and function by addressing the unique problems of the coastal zone, including the lack of clear management and exclusion rights. Just as coastal tenure and catch‐share systems generate meaningful conservation and economic outcomes, it is possible to imagine other market mechanisms that do the same with respect to a variety of other coastal ecosystem goods and services. Rather than solely relying on extracting goods, these approaches could allow communities to diversify ecosystem uses and focus on long‐term stewardship and conservation, while meeting development, food security, and human welfare goals. The creation of ecomarkets will be difficult in many cases, because rights and responsibilities must be devolved, new social contracts will be required, accountability systems must be created and enforced, and long‐term patterns of behaviour must change. We argue that efforts to overcome these obstacles are justified, because these deep changes will strongly complement policies and tools such as Marine Protected Areas, coastal spatial management, and regulation, thereby helping to bring coastal conservation to scale.